2019
DOI: 10.1002/lt.25422
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Measure of Hepatocellular Carcinoma Burden Predicts Tumor Recurrence After Liver Transplantation: The Recurrent Hepatocellular Carcinoma–Initial, Maximum, Last Classification

Abstract: Risk of recurrent hepatocellular carcinoma (rHCC) after liver transplantation (LT) depends on the pre‐LT HCC burden, tumor behavior, and response to locoregional therapy (LRT). In December 2017, LT priority for HCC was expanded to select patients outside the Milan criteria who respond to LRT. Our aims were to develop a novel objective measure of pre‐LT HCC burden (model of recurrent hepatocellular carcinoma–initial, maximum, last [RH‐IML]), incorporating tumor behavior over time, and to apply RH‐IML to model p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…Tumor size and number have been well-recognized risk factors associated with tumor recurrence and long-term survival among patients after curative resection or transplantation for HCC. [27][28][29][30][31][32][33] In fact, both tumor size and number are surrogates of tumor aggressiveness, being strongly associated with presence of microvascular invasion, satellite lesions, and vessels that encapsulate tumor cluster. 34,35 Multifocal HCC may represent either intrahepatic metastasis or multiple primary tumors, suggesting aggressive biological behavior at the time of presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor size and number have been well-recognized risk factors associated with tumor recurrence and long-term survival among patients after curative resection or transplantation for HCC. [27][28][29][30][31][32][33] In fact, both tumor size and number are surrogates of tumor aggressiveness, being strongly associated with presence of microvascular invasion, satellite lesions, and vessels that encapsulate tumor cluster. 34,35 Multifocal HCC may represent either intrahepatic metastasis or multiple primary tumors, suggesting aggressive biological behavior at the time of presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Fifty-eight studies that compared the Milan criteria with other criteria were included in the study. Of these, 41 studies compared the Milan and UCSF criteria 33–45 , 47–51 , 53 , 55–60 , 63 , 64 , 67 , 68 , 70–73 , 76–79 , 83 , 85 , 86 , 90 , 16 studies compared the Milan and UPTS criteria 46 , 52 , 54 , 59 , 61 , 62 , 65 , 66 , 68 , 73 , 74 , 78 , 83 , 84 , 86 , 87 , seven studies compared the Milan and AFP criteria 69 , 75 , 80–82 , 87 , 88 , four studies compared the Milan and MT2 criteria 82 , 87–89 , one study compared the UPTS and MT2 criteria 87 , one study compared the UPTS and AFP criteria 87 , three studies compared the MT2 and AFP criteria 82 , 87 , 88 , and six studies compared the UCSF and UPTS criteria 59 , 68 , 73 , 78 , 83 , 86 .…”
Section: Resultsmentioning
confidence: 99%
“…17 Essential and the last 2-year updates of downstaging HCC before LT are summarized in Table 2. [18][19][20][21][22][23] A recent retrospective cohort of 23 and HCC-specific survival (HR 0.76 [0.59-0.98]) after LT. 18 RFA was highly beneficial for OS and HCC-specific survival after adjusting for related factors. On the other hand, the Kyoto group recently reported that any pretreatment significantly increased the recurrence rate after LT compared with no pretreatment.…”
Section: Downstagingmentioning
confidence: 99%
“…The problem is that the inclusion criteria and downstaging protocols are not systematically fixed . Essential and the last 2‐year updates of downstaging HCC before LT are summarized in Table …”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
See 1 more Smart Citation